Central nervous system tumors - Zamperlini, Gustavo; Klinger, Paulo Henrique dos Santos; Zanette, Antonella; Kuwahara, Cilmara; Epelman, Sidnei; Seber, Adriana; Castro Junior, Cláudio Galvão de (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Central nervous system (CNS) tumors represent one of the most prevalent groups of neoplasms in the pediatric population. Recent advances in molecular biology and neuro-oncology have led to continuous updates in the classification of these tumors, which poses significant diagnostic challenges, particularly in low- and middle-income countries, with limited access to advanced diagnostic tools. The therapeutic approach varies according to tumor subtype, often requiring complex and resource-intensive protocols. One such strategy involves the use of high-dose chemotherapy followed by autologous stem cell rescue, which has shown promise in improving outcomes for select pediatric patients with CNS tumors. However, implementation of this therapy in countries like Brazil faces logistical, financial, and clinical practice challenges. This article aimed to provide a brief overview and suggestions to use high-dose chemotherapy with autologous stem cell transplantation in the treatment of pediatric CNS tumors. We discussed practical considerations for patient selection, and conditioning regimens. Our objectives were to optimize and guide current practices by proposing strategies that maybe feasible in the Brazilian public and private healthcare systems.